2022
DOI: 10.1002/cbf.3732
|View full text |Cite
|
Sign up to set email alerts
|

Bile acid‐based advanced drug delivery systems, bilosomes and micelles as novel carriers for therapeutics

Abstract: Diabetes mellitus affects almost half a billion patients worldwide and results from either destruction of β‐cells responsible for insulin secretion or increased tissue resistance to insulin stimulation and the reduction of glycemic control. Novel drug delivery systems can improve treatment efficacy in diabetic patients. The low aqueous solubility of most oral antidiabetic drugs decreases drug bioavailability; therefore, there is a demand for the use of novel methods to overcome this issue. The application of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 112 publications
0
8
0
Order By: Relevance
“…Different studies revealed that the incorporation of oleic acid into the transethosomes produces more elastic vesicles of smaller vesicular size, higher entrapment efficiency (61), and also increased skin permeation and deposition of the loaded agents, besides enhancing the negative zeta potential of the vesicles (17). The bile salts are widely used permeation enhancer that could withstand alone such as bilosomes (62,63), and could be included in transethosmes (55,64). A study for instance, incorporated sodium deoxycholate in the transethosomal formula and it was found that sodium deoxycholate significantly increased both the entrapment efficiency and the vesicular size that was attributed to the electrostatic repulsion between the bilayers that increased the interbilayer distance (65).…”
Section: Other Components Of Ethosomal Systemmentioning
confidence: 99%
“…Different studies revealed that the incorporation of oleic acid into the transethosomes produces more elastic vesicles of smaller vesicular size, higher entrapment efficiency (61), and also increased skin permeation and deposition of the loaded agents, besides enhancing the negative zeta potential of the vesicles (17). The bile salts are widely used permeation enhancer that could withstand alone such as bilosomes (62,63), and could be included in transethosmes (55,64). A study for instance, incorporated sodium deoxycholate in the transethosomal formula and it was found that sodium deoxycholate significantly increased both the entrapment efficiency and the vesicular size that was attributed to the electrostatic repulsion between the bilayers that increased the interbilayer distance (65).…”
Section: Other Components Of Ethosomal Systemmentioning
confidence: 99%
“…Overall, bilosomes offer several advantages as delivery systems for oral drug delivery, including improved stability, increased bioavailability, and controlled release ( Table 1 ). Ongoing research is focused on optimizing these systems for maximizing efficacy and safety [ 4 , 42 ]. Noticeably, the digestibility, oral bioavailability, and local toxicity and side effects of orally prescribed drugs need to be considered when choosing and developing the proper nanocarrier [ 4 , 42 ].…”
Section: Challenges In the Treatment Of Gastrointestinal Infectionsmentioning
confidence: 99%
“…Ongoing research is focused on optimizing these systems for maximizing efficacy and safety [ 4 , 42 ]. Noticeably, the digestibility, oral bioavailability, and local toxicity and side effects of orally prescribed drugs need to be considered when choosing and developing the proper nanocarrier [ 4 , 42 ]. The ability to encapsulate both the hydrophilic and hydrophobic drugs into the same nanocarrier is a great advantage to take into consideration [ 43 ].…”
Section: Challenges In the Treatment Of Gastrointestinal Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Small-angle X-ray and neutron scattering (SAXS/SANS) measurements of worm-like bile salt–lecithin surfactant mixtures have highlighted the importance of understanding the interplay among curvature, composition, concentration, and electrostatic and hydrophobic interactions, to modulate the structure and growth of these micellar assemblies. The application of bile salt micelles toward improving the solubility of poorly water-soluble drugs, by sequestering the drug inside the hydrophobic micellar core or near the core–shell interface, is greatly facilitated by knowledge of the structural and thermodynamic aspects of these nanocarrier systems. Synergistically interacting mixed surfactant systems have the additional advantage of decreasing the critical micelle concentration (CMC), thereby decreasing the total surfactant concentration needed for drug solubilization, which can improve the toxicological profile of the drug delivery system …”
Section: Introductionmentioning
confidence: 99%